Music in Maxim Munzuk’s life - Karelina, Ekaterina K. (The New Research of Tuva, 2014)
Article presents the musical heritage of Tuvan artist M.M. Munzuk. It reviews his song repertoire, his fieldwork on collecting the people’s songs, about the musical heritage of Munzuk which still awaits it’s time to be published.